New Horizons in Insect Science: Towards Sustainable Pest Management 2015
DOI: 10.1007/978-81-322-2089-3_28
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parasitoids and Predators in the Management of Insect Pests

Abstract: With increasing hazards due to chemical/synthetic pesticides, the only answer to mitigate these ill-effects is use of safe alternatives. Amongst them, use of natural enemies comprising of parasitoids, predators, entomopathogens, etc. as biological control agents is the most effective, environmentally sound and cost-effective pest management approach to control insect pests. It is anticipated that biological control will play an increasingly important role in integrated pest management (IPM) programs as broadsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Parasitoids are depends on or withininsect host for their foods and then ultimately killing the host. They are used as biological control agents it means similar to chemical pesticides but they attain pest management in an environmentally friendly way (Machtinger et al, 2015;Ballal and Verghese, 2015). Different types of beneficial insect parasitoids are wasps, flies, beetles etc.…”
Section: Parasitoidsmentioning
confidence: 99%
“…Parasitoids are depends on or withininsect host for their foods and then ultimately killing the host. They are used as biological control agents it means similar to chemical pesticides but they attain pest management in an environmentally friendly way (Machtinger et al, 2015;Ballal and Verghese, 2015). Different types of beneficial insect parasitoids are wasps, flies, beetles etc.…”
Section: Parasitoidsmentioning
confidence: 99%
“…Parasitoid wasps are essential insects for the biological control of agricultural pests [8]. They lay eggs inside the body of their arthropod hosts, where the immature offspring Parasitoid wasps are essential insects for the biological control of agricultural pests [8].…”
Section: Introductionmentioning
confidence: 99%
“…As well, in many countries, several studies have demonstrated that ants can be key generalist predators of crop pests (El-Keroumi et al, 2010;Fernandes et al, 2010 andSanders &Van Veem, 2011). Wu et al, (2013) and Chandish and Verghese (2015), demonstrated that formicid species are important predators of Lepidoptera eggs and larvae. Also, Diame et al, (2018) reported that ants play a major role in regulating crop-damaging insects.…”
Section: Introductionmentioning
confidence: 99%